2020
DOI: 10.33448/rsd-v9i11.10128
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive effect of amantadine as adjuvant in postoperative analgesia of ovaryhisterectomy in dogs

Abstract: This study aimed to evaluate the preemptive analgesic effect of amantadine on postoperative pain control in female dogs that underwent ovariohysterectomy. Twenty female dog were randomly assigned to two groups of ten. The control group (CONTROL) received oral placebo capsules, while the amantadine (AMANT) group received 5 mg/kg of oral amantadine one hour before sedation. All the animals were premedicated with 3 mg/kg (IM) meperidine, induced with propofol and maintained with isofluorane. The transanesthetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 32 publications
3
11
1
Order By: Relevance
“…With the implementation of FACS, it has been possible to identify subjective states as pain. The tension of the muscles of the face, lips, orbital region, and flattening of the ears are commonly recognized in animals [2,[139][140][141][142][143][144][145][146][147][148][149][150]. This system has been adapted as a veterinary clinical tool (called Grimace Scales) to identify pain in species such as equines [142], chimpanzees [60], macaques [143], sheep [8], rabbits [144], ferrets [145] and rats [33].…”
Section: Changes In Facial Expressions Related To Painmentioning
confidence: 99%
See 1 more Smart Citation
“…With the implementation of FACS, it has been possible to identify subjective states as pain. The tension of the muscles of the face, lips, orbital region, and flattening of the ears are commonly recognized in animals [2,[139][140][141][142][143][144][145][146][147][148][149][150]. This system has been adapted as a veterinary clinical tool (called Grimace Scales) to identify pain in species such as equines [142], chimpanzees [60], macaques [143], sheep [8], rabbits [144], ferrets [145] and rats [33].…”
Section: Changes In Facial Expressions Related To Painmentioning
confidence: 99%
“…DIVAS includes evaluating changes in facial expression and behaviors and vocalizaderived from pain, such as changes in posture, inactivity, or aggressiveness. A scale from 0 to 100 mm has been used to assess the effects of preemptive analgesia in routine surgeries such as ovariohysterectomy; a patient with a score of 40 mm requires analgesic [148]. Likewise, it has been used to estimate pain intensity in canines undergoing various surgical procedures, such as exploratory laparotomy, hemilaminectomies, osteotomies, and atlantoaxial subluxation [149].…”
Section: Changes In Facial Expressions Related To Painmentioning
confidence: 99%
“…With the implementation of FACS, it has been possible to identify subjective states such as pain. The tension of the muscles of the face, lips, orbital region, and flattening of the ears are commonly recognized in animals [ 2 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 ]. This system has been adapted as a veterinary clinical tool (called Grimace Scales) to identify pain in species such as equines [ 142 ], chimpanzees [ 60 ], macaques [ 143 ], sheep [ 8 ], rabbits [ 144 ], ferrets [ 145 ] and rats [ 33 ].…”
Section: Changes In Facial Expressions Related To Painmentioning
confidence: 99%
“…DIVAS includes evaluating changes in facial expression and behaviors and vocalizations derived from pain, such as changes in posture, inactivity, or aggressiveness. A scale from 0 to 100 mm has been used to assess the effects of preemptive analgesia in routine surgeries such as ovariohysterectomy; a patient with a score of 40 mm requires analgesic intervention [ 148 ]. Likewise, it has been used to estimate pain intensity in canines undergoing various surgical procedures, such as exploratory laparotomy, hemilaminectomies, osteotomies, and atlantoaxial subluxation [ 149 ].…”
Section: Changes In Facial Expressions Related To Painmentioning
confidence: 99%
“…In addition, [25] concluded that the combination of amantadine and non-steroidal anti-in ammatory drugs, as part of a multimodal analgesic treatment, improved physical activity in dogs with refractory osteoarthritis. Other studies in dogs demonstrated that the preemptive administration of amantadine reduced the analgesic requirement in dogs submitted to OVH [12], as well as being effective as a multimodal therapy in the treatment of neuropathic pain in a dog [21]. In the feline species, the work carried out by Snijdelaar and Koren [22] demonstrated satisfactory results from the daily use of amantadine, with 5mg/kg being administered orally for three weeks, in cats with osteoarthritis, which showed improvement in quality of life.…”
Section: Introductionmentioning
confidence: 96%